2015
DOI: 10.1097/sap.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Use of Platelet-Rich Plasma and Adipose-Derived Stem Cells on Fat Graft Survival

Abstract: Adipose-derived stem cells combined with PRP can enhance the survival of transplanted fat tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…64,65 PRP and ASCs act synergistically when combined in rodents, with better retention combined than when either are used independently. 66 The addition of PRP to human fat grafts has also been promising, with multiple reports of improved volume retention. 47,[67][68][69][70] However, findings remain far from consensus, as evidenced by a recent trial by Rigotti and colleagues, 71 which reported no benefit when adding PRP to ASC-enriched fat grafts for facial rejuvenation.…”
Section: Platelet-rich Plasmamentioning
confidence: 98%
“…64,65 PRP and ASCs act synergistically when combined in rodents, with better retention combined than when either are used independently. 66 The addition of PRP to human fat grafts has also been promising, with multiple reports of improved volume retention. 47,[67][68][69][70] However, findings remain far from consensus, as evidenced by a recent trial by Rigotti and colleagues, 71 which reported no benefit when adding PRP to ASC-enriched fat grafts for facial rejuvenation.…”
Section: Platelet-rich Plasmamentioning
confidence: 98%
“…In the ‘three zone’ theory suggested by Yoshimura et al (38), the survival of fat grafts is largely dependent on adipose tissue regeneration post-transplantation, and CD34-positive cells are very likely the seed cells for adipogenic progression. Therefore, recent studies (14,39) have focused on the therapeutic effects of adipose-derived cells, including stromal vascular fraction and ADSCs, on fat grafts. These cells may improve tissue outcomes by increasing the vascularity and the secretion of growth factors that improve tissue survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the combination of ASCs and PRP has been reported to yield several beneficial effects, e.g., in bone regeneration [ 21 ] and fat graft survival [ 22 ]. Particularly in wound management in pathological situations, combination therapy on ASC/PRP was suggested [ 6 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%